2001
DOI: 10.1002/1099-0690(200101)2001:1<187::aid-ejoc187>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of 4-Fluoro-5-(perfluoroalkyl)pyrazoles from Organofluorosilicon Building Blocks

Abstract: A series of 4‐fluoro‐5‐(perfluoroalkyl)pyrazoles has been prepared by heterocyclization of hemiperfluoroenones 3 or synthetic equivalents 1 and 2 with methylhydrazine. Compounds 1−3 were obtained by reaction of acylsilanes and perfluoroorganometallic reagents. The fluorinated pyrazoles could also be prepared in a one‐pot reaction from the starting acylsilanes. This method is very general and has been applied to aromatic, aliphatic and carbohydrate derivatives, as well as to bis(pyrazole) derivatives. The react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The proposed mechanism suggested that the reaction took place by the nucleophilic attack of the phosphorus atom of phosphite at CH=N bond, generating the α‐hydrazinophosphonate 9A as the intermediate, which also existed in the enolic form 9B . The latter intermediate 9B underwent nucleophilic attack of the OH group at the phosphonate moiety to eliminate the ethanol molecule , thus affording the nonisolable intermediate 12 , which underwent auto‐oxidation to afford the pyrazolyloxadiazaphosphorine 13 as the stable orange crystalline solid (Scheme ). Its elemental analysis and spectroscopic results were consistent with the assigned structure 13 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed mechanism suggested that the reaction took place by the nucleophilic attack of the phosphorus atom of phosphite at CH=N bond, generating the α‐hydrazinophosphonate 9A as the intermediate, which also existed in the enolic form 9B . The latter intermediate 9B underwent nucleophilic attack of the OH group at the phosphonate moiety to eliminate the ethanol molecule , thus affording the nonisolable intermediate 12 , which underwent auto‐oxidation to afford the pyrazolyloxadiazaphosphorine 13 as the stable orange crystalline solid (Scheme ). Its elemental analysis and spectroscopic results were consistent with the assigned structure 13 .…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of compound 21 with P,P‐dimethylphosphinic hydrazide in boiling ethanol afforded the pyrazolylpyrazoline intermediate 23 which underwent aromatization via auto‐oxidation to give 5‐amino‐1‐(dimethylphosphoryl)‐3‐(1,3‐diphenyl‐1 H ‐pyrazol‐4‐yl)‐1 H ‐pyrazole‐4‐carbonit‐rile ( 24 ) as brown crystals (Scheme ). Interestingly, the latter compound 24 was also obtained from the treatment of the diethyl pyrazolyl phosphonate 22 with P,P‐dimethylphosphinic hydrazide in boiling ethanol (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…11 afforded the expected 4-trifluoromethyl pyridazinones 9a,c-e in excellent yields (Table 1), the structure of which was confirmed by spectral data. The appearance in 13 C NMR spectra of a quaternary carbon at 129-130 ppm (quartet, 2 J C,F = 32.5 Hz) and of a vinylic CH at 128-132 ppm (q, 3 J C,F = 4.6-4.8 Hz) clearly showed the dehydrogenation reaction.…”
Section: Methodsmentioning
confidence: 96%
“…Substituted hydrazines led regioselectively to compounds substituted on nitrogen N-2, indicating hydrazone formation in the first step. The new heterocycles 8a-e were characterized by usual spectral analyses: IR (C=O = 1672-1686 cm -1 ), MS, 19 F NMR (δ CF3 ca -69 ppm, d, 3 J F,H = 8.5-9.5 Hz), 1 H NMR and 13 C NMR (δ C=N = 147-152 ppm; δ C=O = 158-161 ppm, q, 3 J C,F = 2.0 Hz). 11 afforded the expected 4-trifluoromethyl pyridazinones 9a,c-e in excellent yields (Table 1), the structure of which was confirmed by spectral data.…”
Section: Methodsmentioning
confidence: 99%
“…The insertion of the -amino-, -difluoroketone 7 [18] unit into a peptide proved to be successful in the design of enzyme inhibitors such as protease inhibitors [26]. The similar , -unsaturated intermediates 9, which were obtained by the treatment of acylsilanes 2 with perfluoro organolithium reagents 10, reacted with methylhydrazine to afford a series of 4-fluoro-5-(perfluoroalkyl)pyrazoles 11 in 53-69% yields (Scheme 2) [27]. The similar , -unsaturated intermediates 9, which were obtained by the treatment of acylsilanes 2 with perfluoro organolithium reagents 10, reacted with methylhydrazine to afford a series of 4-fluoro-5-(perfluoroalkyl)pyrazoles 11 in 53-69% yields (Scheme 2) [27].…”
Section: One-pot Synthesis Of Gem-difluorocarbonyl Building Blocksmentioning
confidence: 99%